Formation and safety of 2-dodecylcyclobutanone, a unique radiolytic product in irradiated beef - Gadgil, P.; Smith, J. Scott (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Treating food with ionizing radiation improves product safety and helps maintain quality. The main selling point of irradiated foods is that it is microbially safe. Beginning in October 2002, companies could petition the FDA for permission to use terms like "electronic pasteurization" on the labeling for irradiated foods. Consumers are already familiar with pasteurization and they associate the term with a safe product. There needs to be a protocol in place to test for irradiation to verify that products meet regulatory requirements. Being able to differentiate between irradiated and nonirradiated food will aid in proving the authenticity and safety of irradiated products and in detecting mislabeled products. In November 2003, Excel Corporation (Dodge City, KS) voluntarily recalled 26,000 pounds of ground beef that was mislabeled as irradiated. The incident appears to be the first case of its kind, and it emphasizes the need for a method that can reliably distinguish between irradiated and non-irradiated foods. At the doses currently approved for food irradiation, the only unique radiolytic products that have been identified are alkylcyclobutanones (2-ACBs). These are cyclic compounds formed by rearrangement of fatty acids when exposed to irradiation. They are found in a wide variety of lipid-containing foods and have been universally accepted as indicators of irradiation exposure. Recent studies have raised the possibility of 2-ACBs being weak genotoxins or cancer promoters when tested at high concentrations. Numerous long-term and short-term toxicity tests have demonstrated the safety of irradiated foods. In spite of these reports, some claim that irradiated foods are unsafe and have used the previous studies as proof that alkylcyclobutanones are carcinogenic. Therefore, more studies evaluating the toxicity of these chemicals at high and low concentrations are needed to conclusively prove their safety. Accordingly, the objectives of this research were to evaluate the formation of 2- dodecylcyclobutanone (2-DCB), the alkylcyclobutanone formed from palmitic acid, in irradiated ground beef, and to assess its toxicity.
Keywords: Beef; Cattle; 2-dodecylcyclobutanone (2-DCB); Irradiated beef